Implementasi Kebijakan Digitalisasi Arsip Pada Dinas Perpustakaan Dan Kearsipan Kabupaten Karawang - Safira Nur Sudrajat; Dadan Kurniansyah; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2023)
The rapid development of information technology in the digital era has a significant impact on archives. An organization's ability to adapt to electronic records management is essential to meet information needs. The Karawang Regency Library and Archives Office carries out the implementation of the archive digitization policy in accordance with PP Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE) to realize an integrated and comprehensive electronic-based government system to achieve a high-performing public service bureaucracy. However, the Karawang Regency Library and Archives Office has several obstacles that must be faced, namely lack of communication between employees. Lack of human resources both in terms of numbers and abilities and some supporting facilities, lack of adaptation to changes and others. The implementation of the archive digitization policy by the Karawang Regency Library and Archives Office is expected to realize an integrated and comprehensive electronic-based government system to achieve a high-performing public service bureaucracy to facilitate all integrated data collection processes. The purpose of this study was to determine and analyze policy implementation in terms of communication, resources, disposition, and bureaucratic structure at the Karawang Regency Library and Archives Office. This research uses qualitative research methods with a descriptive approach. The theory used is the Edwards III model of policy implementation theory by considering four critical factors or variables in implementing public policies, namely Communication, Resources, Disposition, and Bureaucratic Structure. The results showed the achievement of the implementation of the archive digitization policy by the Karawang Regency Library and Archives Office in accordance with applicable regulations.